Does Creative Arts Therapy Improve Distressing Symptoms in Children with Cancer? A Synthesis of Extant Literature. (January 2022) - Raybin, Jennifer L.; Harnke, Ben; Hendricks-Ferguson, Verna
Introduction: Children with cancer experience symptom distress which has been correlated with decreased quality of life (QOL). Creative arts therapy (CAT) encompasses the therapeutic use of creative arts which may improve QOL among children with cancer by affecting symptoms. Therefore, the research question was asked: Does CAT affect symptoms of pain, nausea, fatigue, anxiety, and mood in children with cancer?Methods: Based on the study question, a comprehensive literature search of PubMed, CINAHL, PsycINFO, and Embase was completed. Inclusion criteria limited articles to specific symptom outcomes in two-group intervention studies in the English language. Selected articles were confirmed for inclusion by the study team, followed by group discussion to develop matrices with levels of evidence based on the Grading of Recommendations Assessment, Development, and Evaluation (Grade) guidelines.Results: Initial searches revealed 1, 391 articles, screened to 44 for systematic review. Based on the inclusion criteria, 11 articles remained. Four studies had evidence levels graded as low, three were low to moderate, and four were moderate. Outcomes of mood and anxiety were measured in five studies, pain in four, fatigue in two, and nausea in one study.Discussion: Psychological outcomes were measured more commonly than physical outcomes. Evidence reached a moderate grade in four studies.Summary: Through this synthesis of intervention studies with CAT in children with cancer, improvement in distressing symptoms has potential, but the state of the science for symptom management with CAT could be strengthened for nurses to promote CAT to improve QOL among children with cancer.